Capacity assessment of barangay violence against women (VAW) desk offices in Calamba City, Laguna - Consignado, Gillian D. 1989 (National College of Public Administration and Governance, University of the Philippines Diliman, 2019)
Violence against women (VAW) remains a pervasive concern in the Philippines. The passage of laws and local policies to address these issues are meant to address these wrongful practices. The barangay VAW desk office, being the implementing arm of the local government units (LGUs) in handling gender-sensitive matters at the grassroots, performs an important role in addressing these issues.